Fractional Discrete Modeling and Numerical Analysis of Hepatitis B and C Dynamics with Neural Network Approximation (European Journal of Pure and Applied Mathematics, 2025)
This paper is devoted to analysis the dynamics of hepatitis B and C through some mathematical difference equations. Serious viral illnesses that mainly affect the liver, hepatitis B and C can cause inflammation and even damage to the liver. Hepatitis B can spread by bodily fluids such as semen or vaginal fluid, even though both are blood-borne. While hepatitis C can be cured with medication, hepatitis B can be prevented with vaccine. We formulate a mathematical model of the mentioned disease through fractional difference equations using the Caputo fractional difference operator (CFDO). Existence theory, Ulam-Hyers (UH) stability and numerical investigation are deduced. Further,  analysis based on artificial intelligence (AI) is considered. We have used neural networks (NNs) based investigations to conduct our study.  Various graphical illustrations are given to demonstrate our results. For our analysis we use Matlab software with 2023 version.